An Analysis of Students' Capability in Mastering Vocabulary at the Seventh Grade of SMP Muhammadiyah 2 Masaran, Sragen in 2015/2016 Academic Year - Hartono, Aprilya Nirvan; , Aryati Prasetyarini, S.Pd, M.Pd; , Siti Fatimah, S. Pd, M. Hum (2015)
This research aims at analyzing the students' capability in mastering vocabulary at the seventh year of SMP Muhammadiyah 2 Masaran, Sragen. Specifically, the study is conducted to describe 1) the number of words mastered by the students 2) the students' capability in pronouncing of words and 3) the students' capability in using words. The writer gets the data from test. The methods of collecting data is test. This research uses descriptive qualitative. The technique for analyzing data: 1) giving test 2) analyzing the descriptive research. The result of the an analysis shows that: 1) the number of words mastered by the students is 2700 words at seventh grade of SMP Muhammadiyah 2 Masaran, Sragen. 2) the students' capability in pronouncing of words by the students. Pronunciation of the students with vocabulary size test. The percentage of high scores is 39.39% for 13 students 2700 words is good. 3) the skill students in using words is good. The student's only understood 30 words from 50 words in exercise. Keywords: vocabulary mastery, vocabulary size test, capability&pronouncing words